Analysis of the Application of Additive Manufacturing for On-Demand Repair and Maintenance of Naval Equipment in Remote Maritime Operations - Yustiani Frastika; Frisca Mareyta Pongoh; Dedtri Anwar; Arika Palapa; Jaya Alamsya (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
Background: Traditional naval maintenance strategies rely on centralized supply chains and pre-manufactured spare parts, leading to long repair downtimes and logistical inefficiencies, particularly for vessels operating in remote maritime regions. Additive manufacturing (3D printing) offers a disruptive alternative by enabling on-demand production of spare parts, reducing dependence on external suppliers, and enhancing fleet self-sufficiency. However, material durability, operational feasibility, and cost-effectiveness remain underexplored for naval applications. Original Value: This research advances the study of AM in naval engineering, assessing its practical viability beyond theoretical potential. Unlike previous studies focusing on commercial maritime applications, this study evaluates 3D printing’s impact on naval fleet readiness, supply chain resilience, and sustainability. Objectives: The study investigates how 3D printing can optimize naval maintenance efficiency, specifically analyzing its feasibility, material performance, cost implications, and logistical advantages. Methodology: A qualitative-empirical approach was used, combining material performance testing, expert interviews, and operational case studies to evaluate mechanical durability, economic feasibility, and AM integration challenges. Results: Findings indicate that AM reduces repair downtime by 40%, lowers part procurement costs by 30–50%, and enhances supply chain resilience. However, material limitations and infrastructure readiness remain key adoption challenges. Conclusions: Hybrid AM adoption—where 3D printing supplements rather than replaces traditional manufacturing—offers the most practical near-term approach for naval fleets. Strategic investment in material research, onboard AM training, and fabrication infrastructure will enhance fleet efficiency, reduce environmental impact, and future-proof maritime maintenance strategies.